CORRELATION OF OBSTRUCTIVE JAUNDICE, SERUM GAMA-GLUTAMYL TRANSFERASE AND ALKALINE PHOSPHATASE IN CHILDREN BELOW OF 14 YEARS IN SOUTHERN PUNJAB. : J Peop Univ Med Health Sci. 2025:15(3), 55-63. http://doi.org/10.46536/jpumhs/2025/15.03.658 - Nasir Islam1, Madiha Rehman2, Shahid Ishaq3, Muhammad Salman Zafar4, Ghulam Hussain5, Muhammad Awais Niaz6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Obstructive jaundice in children is a significant clinical concern that requires timely diagnosis to prevent long-term hepatobiliary complications. OBJECTIVE: This study aimed to assess the correlation between serum Gamma-Glutamyl Transferase (GGT), Alkaline Phosphatase (ALP), and the presence of obstructive jaundice in children under 14 years of age in Southern Punjab. METHODS: A cross-sectional study was conducted on 250 pediatric patients diagnosed with jaundice. Demographic, clinical, diagnostic, and laboratory data were collected. Serum GGT, ALP, and bilirubin levels were measured. Patients were categorized into obstructive and non-obstructive groups based on imaging and clinical diagnosis. Statistical analyses included correlation, group comparisons, logistic regression, and ROC curve analysis. RESULTS: The mean age was 7.13 ± 3.94 years; 50.8% were male. Dark-colored urine (62%) and pruritus (58%) were the most common symptoms. Ultrasonography revealed dilated bile ducts in 41.2% and gallstones in 24.0%. The mean GGT and ALP levels were 306.48 ± 169.65 U/L and 780.71 ± 420.45 IU/L, respectively. A strong positive correlation was found between GGT and ALP (r = 0.68, p < 0.001), and both were significantly elevated in obstructive jaundice cases (p < 0.001). Logistic regression showed GGT (OR = 1.014), ALP (OR = 1.005), and direct bilirubin (OR = 1.186) as independent predictors. ROC analysis yielded AUCs of 0.91 for GGT and 0.88 for ALP. CONCLUSION: GGT and ALP are reliable, accessible markers for identifying obstructive jaundice in pediatric patients, especially in low-resource settings. Their integration into early diagnostic protocols can significantly improve clinical outcomes.